Large deletion at the CDC73 gene locus and search for predictive markers of the presence of a CDC73 genetic lesion - Muscarella, Lucia Anna; Turchetti, Daniela; Fontana, Andrea; Baorda, Filomena; Palumbo, Orazio; la Torre, Annamaria; de Martino, Danilo; Franco, Renato; Losito, Nunzia Simona; Repaci, Andrea; Pagotto, Uberto; Cinque, Luigia; et al. (Oncotarget, 2018)
The Hyperparathyroidism with Jaw-Tumours syndrome is caused by mutations of the gene: it has been suggested that early onset of the disease and high Ca levels may predict the presence of a mutation. We searched for large deletions at the locus in patients with: HPT-JT (nr 2), atypical adenoma (nr 7) or sporadic parathyroid carcinoma (nr 11) with a specific MLPA and qRT-PCR assays applied on DNA extracted from whole blood. A Medline search in database for all the papers reporting a gene mutation, clinical/histological diagnosis, age at onset, Ca , PTH levels for familial/sporadic cases was conducted with the aim to possibly identify biochemical/clinical markers predictive, in first diagnosis, of the presence of a gene mutation. A novel genomic deletion of the first 10 exons of the gene was found in a 3-generation HPT-JT family, confirmed by SNP array analysis. A classification tree built on the published data, showed the highest probability of having a mutation in subjects with age at the onset < 41.5 years (44/47 subjects, 93.6%, had the mutation). Whereas the lowest probability was found in subjects with age at the onset ≥ 41.5 years and Ca levels <13.96 mg/dL (7/20 subjects, 35.0%, had the mutation, odds ratio = 27.1, < 0.001). We report a novel large genomic CDC73 gene deletion identified in an Italian HPT-JT family. Age at onset < 41.5 ys and Ca > 13.96 mg/dL are predictive for the presence of a CDC73 genetic lesion.